A New Anthropomorphic Mannequin for Efficacy Evaluation of Thoracic Protective Equipment Against Blast Threats - Boutillier, Johanna; Cardona, Venetia; Magnan, Pascal; Ogier, Michael; De Mezzo, Sébastien; Montespan, Florent; Menini, William; Mosnier, Joël; Naz, Pierre; Prat, Nicolas J. (Frontiers in Bioengineering and Biotechnology, 2022)
Exposure to blast is one of the major causes of death and disability in recent military conflicts. Therefore, it is crucial to evaluate the protective capability of the ballistic-proof equipment worn by soldiers against the effects of blast overpressure (i.e. primary blast injuries). A focus will be made on thoracic protective equipment (TPE). An anthropomorphic mannequin, called BOPMAN, and anesthetized swine both wearing soft, hard or no ballistic protection, were subjected to an open-field high-intensity blast. For swine, thoracic wall motion (acceleration and velocity) was recorded during blast exposure and severity of lung injury was evaluated postmortem. Different data were collected from BOPMAN thoracic responses, including reflected and internal pressure, as well as the force at the rear face of the instrumented part. The severity of blast-induced lung injuries (contusion extent, Axelsson Severity Scale) and the thoracic wall motion were decreased in animals protected with thoracic ceramic hard plates as compared to those wearing soft or no protection. There was a clear trend towards greater lung injury in animals protected with the soft body armor used, even when compared to unprotected animals. In line with these experimental data, the measured force as well as the force impulse measured using BOPMAN were also decreased with a ceramic hard plate protection and increased when a soft ballistic pack was used compared to no protection. Comparison of data collected on BOPMAN and swine equipped with the same protection level revealed that those two force parameters were well correlated with the level of blast-induced lung injury (force, R² = 0.74 and force impulse, R²=0.77, p<0.05). Taken together, our results suggest that the force and the force impulse data from BOPMAN may help estimate the efficiency of existing TPE regarding lung protection under blast exposure and may represent an important tool for development of future TPE.